Enhanced generation of H2O2 and radicals on Co9S8/partly-graphitized carbon cathode for degradation of bio-refractory organic wastewater. (20th September 2016) - Lin, Yuhui; Yu, Jia; Xing, Zipeng; Guo, Xiaolei; Yu, Xiujuan; Tang, Bo; Zou, Jinlong
Graphical abstract: Highlights: Co9 S8 /PGC as EAOPs cathode was derived from waste pomelo skins as carbon source. More catalytic active sites were formed in Co9 S8 /PGC with porous structure. Synergistic effect between Co9 S8 and PGC induced high selectivity for 2e − ORR (H2 O2 ). Mixed-valence nature of Co 2+ /Co 3+ in Co9 S8 promoted the OH generation from H2 O2 . Co9 S8 /PGC exhibited high performance for phenol and ceftazidime degradation. Abstract: In electrochemical advanced oxidation processes (EAOPs), the hydrogen peroxide (H2 O2 ) could be in-situ generated from the two-electron (2e − ) oxygen reduction reaction (ORR), which was then converted to OH radicals in the role of cathode catalyst. To improve the efficiency of H2 O2 generation, cobalt sulfide/partly-graphitized carbon (Co9 S8 /PGC) composites as EAOPs cathodes were synthesized via a simple simultaneous carbonization method. The structural and electrochemical properties of Co9 S8 /PGC were investigated. Results demonstrated that Co9 S8 with coexistence of Co 2+ /Co 3+ was tightly embedded into the PGC skeleton. Abundant oxygen-containing groups on the PGC surface could improve the wettability and hydrophilicity of the Co9 S8 /PGC (800 °C), contributing to the formation of more catalytic active sites in the porous structure. Synergistic effect between Co9 S8 and PGC could improve the electron transfer efficiency and O2 mass transfer by increasing the contact interface area between electrode and electrolyte, inducing the high selectivity for 2e − ORR. The mixed-valence nature of Co9 S8 (Co 2+ /Co 3+ ) exhibited high catalytic activity for promoting the OH generation from H2 O2 . Degradation rates of phenol and TOC removal rate of ceftazidime reached approximately 89.1 and 84.3% at 120 and 480 min, respectively, indicating that Co9 S8 /PGC cathode had promise for further application.